2006
DOI: 10.1529/biophysj.106.088070
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Signatures of Heterogeneous Protein Ensembles Revealed by MD Simulations of 2DIR Spectra

Abstract: A model for the calculation of amide I FTIR and 2DIR spectra taking into account fluctuations in hydrogen bonding and structure from molecular dynamics (MD) simulations is tested on three systems. It is found that although the homogeneous lineshape approximation yields satisfactory FTIR spectra, 2DIR spectra are sensitive to the inhomogeneity naturally present in any solvated protein and the common approximations of a static structure and averaged-effect solvent are invalid. By building on the local amide Hami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
126
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 68 publications
8
126
2
Order By: Relevance
“…This Z-shape like structure is much less pronounced than observed for the ideal β-sheet structure [18,19]. Such features were also found in the studies of other β-hairpin peptides [24,29]. In the 2D spectra in Fig.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This Z-shape like structure is much less pronounced than observed for the ideal β-sheet structure [18,19]. Such features were also found in the studies of other β-hairpin peptides [24,29]. In the 2D spectra in Fig.…”
Section: Resultssupporting
confidence: 71%
“…The 2DIR technique distinguishes β-sheet structures by producing Z shape like spectra [18,19] when this particular structural motif is present. In the past decades a number of 2DIR studies have been reported of peptides and proteins in solution [16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] or confined in membranes [34][35][36][37][38], revealing structural details and conformational changes from femtosecond (fs) to nanosecond (ns) time scales, and the nature of dynamic environments. For the structure determination of peptides that are in gas phase or micro-solvated (surrounded by few solvent molecules) the mid-infrared spectroscopic technique has become a promising tool [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…29 Early models for amide I frequencies employed simple geometric criteria such as hydrogen bond count and length; 9,[30][31][32][33] although these models have proven intuitively useful and reasonably accurate for simple calculations, 34 they are generally regarded as insufficient for detailed spectral simulations. 35 Most current vibrational frequency models are based on a linear mapping of frequency against various combinations of electrostatic variables evaluated at different positions within the peptide group…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] This method exploits the linear correlation found between the C=O bond length, stretching frequency and electrostatic potential at the atoms of NMA, 18,31,32 which provides a link between perturbation of molecular (and electronic) structure by the electric field of the solvent and the resulting shift of the vibrational frequency. Parametrized electrostatic calculations using the building block approach have been used in protein amide I sim-ulations of ubiquitin, 10,33 other proteins 34 as well as polypeptides in membrane environment. 29,35 These calculations are generally combined with MD simulations that provide coordinate trajectories, which are then utilized for calculating instantaneous normal modes and the resulting spectral line shapes.…”
Section: Introductionmentioning
confidence: 99%